Health-related quality of life and symptoms of chronic myeloid leukemia patients after discontinuation of tyrosine kinase inhibitors: results from the EURO-SKI Trial - Efficace, Fabio; Mahon, Francois-Xavier; Richter, Johan; Piciocchi, Alfonso; Cipriani, Marta; Nicolini, Franck E.; Mayer, Jiri; Zackova, Daniela; Janssen, Jeroen J. W. M.; Panayiotidis, Panayiotis; Vestergaard, Hanne; Koskenvesa, Perttu; et al. (Leukemia, 2024)
Limited data is available on the health-related quality of life (HRQoL) and symptoms of patients with chronic myeloid leukemia (CML) who are in treatment-free remission (TFR). We herein report HRQoL results from the EURO-SKI trial. Patients who had been on tyrosine kinase inhibitors (TKIs) therapy for at least 3 years and achieved MR4 for at least 1 year were enrolled from 11 European countries, and the EORTC QLQ-C30 and the FACIT-Fatigue questionnaires were used to assess HRQoL and fatigue respectively. Patients were categorized into the following age groups: 18-39, 40-59, 60-69 and ≥70 years. Of 728 patients evaluated at baseline, 686 (94%) completed HRQoL assessments. The median age at TKI discontinuation was 60 years. Our findings indicate that HRQoL and symptom trajectories may vary depending on specific age groups, with younger patients benefiting the most. Improvements in patients aged 60 years or older were marginal across several HRQoL and symptom domains. At the time of considering TKI discontinuation, physicians could inform younger patients that they may expect valuable HRQoL benefits. Considering the marginal improvements observed in patients aged 60 years or above, it may be important to further investigate the value of TFR compared to a lowest effective dose approach in this older group of patients.